Cancer and COVID-19: ethical issues concerning the use of telemedicine during the pandemic - Lucas Huret; Henri-Corto Stoeklé; Asmahane Benmaziane; Philippe Beuzeboc; Christian Hervé (BMC, 2022)
Abstract The lockdown imposed in France during the first wave of the COVID-19 pandemic wreaked havoc with access to healthcare. From March 2020 onwards, the oncologists of Foch Hospital, like many others at hospitals throughout the world, were obliged to adapt to the new conditions, including, in particular, the impossibility of seeing patients in classic consultations for the diagnosis and treatment of cancer. Patients with cancer are particularly susceptible to this new virus, due to their immune status, and this made it difficult to carry out standard hospital visits for these patients. Some patients refused to come to the hospital, whereas the doctors decided, for others, that consultation conditions at the hospital were not sufficiently safe, with sanitary measures that had yet to be precisely defined. Telemedicine was one of the adaptations adopted during this period. This mode of consultation was little used before the pandemic, for various reasons, and reimbursement was not automatic. This new approach proved to have limitations as well as advantages, as demonstrated by our empirical ethics research study, a retrospective qualitative survey of the doctors of the oncology and supportive care departments of Foch Hospital, performed during July 2021. The interview grid was based on the studies on telemedicine, oncology, COVID-19 and empirical ethics available at the time. Based on the experience gained in this domain during the first wave of the epidemic, which hit France between March and June 2020, we identified three eligibility criteria for consultations in telemedicine: the consultation concerned should not be the first consultation, the patient should be a known patient that the doctor trusts not to minimize the description of symptoms, and the results of the patient's evaluations and examinations must be good. It may be appropriate to continue the use of teleconsultation in the future, provided that these criteria are respected.